Impact of nutrient level and seed density on the yield of some winter wheat varieties - Kristó István (Review on agriculture and rural development, 2019)
The effects of four different nutrient levels (60 kg ha-1 N, 0 kg ha-1 P2O5, 0 kg ha-1 K2O; 90 kg ha-1 N, 30 kg ha-1 P2O5, 30 kg ha-1 K2O; 120 kg ha-1 N, 60 kg ha-1 P2O5, 60 kg ha-1 K2O; 150 kg ha-1 N, 60 kg ha-1 P2O5, 60 kg ha-1 K2O), as well as three different seeding rates (300, 500 and 700 seeds m-2 ) on different winter wheat breeds have been investigated in this publication. The research was established in one growing season (2017/2018), with 5 winter wheat varieties (GK Arató, GK Bagó, Cellule, Lithium, GK Petur), in 4 repeats, on 10 square meter random layout plots in the research farm of the Department of Field Crops Research of National Agricultural Research and Innovation Centre, in Szeged-Öthalom. We determined the yield and evaluated our results with analysis of variance according to the different nutrient levels and seeding rates. Increasing the seed density, the yield of winter wheat increased too, in a decreasing rate. Increased nutrient inputs resulted in higher yields. The reaction to the fertilizers was very different among the varieties, we could show different yield order at different nutrient levels and seed density. Our results proved that the use of different varieties and agrotechnical elements cause a big difference in yield, which also determines the economic efficiency of the farm.